PENGARUH STRES KERJA, KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DINAS PERINDUSTRIAN DAN PERDAGANGAN SEMARANG - Sunita, 10.05.51.0071; Muhaimin, Muhaimin (Students Journal of Economic and Management, 2014)
Research with the title work stress, transformational leadership, and motivation to work, the employees performance is a study that is used to determine and analyze whether work stress variables, transformational leadership, and motivation to work, the Department of Industry and Trade Semarang has a partial influence on employee performance. The samples used in this study were 80 respondents. Sampling technique used was simple random sampling is the selection of a random sample basis without regard to existing strata in the population. Datacollected were tested beforehand using validity and reliability in order to obtain valid and reliable results that can be used in subsequent testing. Further analysis the authors use regression testing to explain the relationship between the independent and dependent variables. The result is work stress (X1), transformational leadership (X2), work motivation (X3) and a significant positive effect on employee performance (Y). From the results of the regression equation that work motivation has the greatest influence and job stress has least influence. Results of test of determination obtained for 0.349 or 34,9%, indicating that the magnitude of the effect of work stress, transformational leadership andwork motivation on employee performance by 34,9%, while the remaining (100% - 34,9% = 65,1%) indicates that the variable performance of employees affected by variables other. This study has limitations that the variables used only in the work stress variables, transformational leadership, work motivation,while there are many other factors that can affect the performance of the employee. In addition, this study only examined the employee at the Department of Industry and Trade of Semarang. Therefore, further research is recommended to consider other variables that have not been found in this study and wider sampling.Keywords: Job Stress, Transformational Leadership, Work Motivation, Employee Performance